Albania : Enhancing Tax Administration Capacity During Challenging Times. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2022)
The purpose of this mission was to assist the General Directorate of Taxes (GDT) in taking stock of reform efforts and provide advice on future efforts. In recent years, the GDT made solid progress in realizing its reform agenda. The mission took stock of the reform achievements and identifies areas which require further improvement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Albania